Scenarios of population change in the coastal Ganges Brahmaputra Delta (2011-2051) - Sylvia Szabo; Dilruba Begum; Sate Ahmad; Zoe Matthews; Peter Kim Streatfield (Asia-Pacific Population Journal, 2016)
This paper provides an overview of population dynamics and scenarios of population change in the environmentally vulnerable coastal Ganges Brahmaputra Delta region. The main data sources used for the study include the most recent and historical census data, data from the Sample Vital Registration System (SVRS) and Demographic and Health Surveys (DHS). The research adopts the standard cohort component approach for population projections and provides population estimates for the period from 2011 to 2051. Research outcomes include scenarios of future population change in the coastal Ganges Brahmaputra Delta region and district-level population projections by age and sex. The results show that population growth is likely to continue in some, but not all, districts in the study area. The results also suggest that future migration flows are most likely to be the deciding component of population change in the study area. Given the expected shifts in population distribution and population structure, policy initiatives will have to address the challenges related to informal settlements and population ageing.